# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime \prime }+4 y^{\prime \prime }+5 y^{\prime } = {\mathrm e}^{-2 x} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }-2 y^{\prime } = {\mathrm e}^{-2 x} \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime } = x^{2} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = x^{2} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = x \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = x^{2} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = x^{2} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+4 y^{\prime } = {\mathrm e}^{x}+\sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+y^{\prime \prime \prime \prime } = x^{2}
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+3 y^{\prime }-2 y = {\mathrm e}^{x} x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime } = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime } = x \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime } = x \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = x^{2} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+3 y = x^{2} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = \sin \left (2 x \right ) x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime } = x^{3} \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime } = x \,{\mathrm e}^{2 x} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = x \,{\mathrm e}^{2 x} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime } = x^{2} {\mathrm e}^{-x} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }-16 x y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+5 x y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-3 x y^{\prime }-18 y = \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-3 x y^{\prime }+2 y = \ln \left (x^{2}\right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 x y^{\prime }+y = 1-x
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-x y^{\prime }+y = \frac {1}{x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 4 x +\sin \left (\ln \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+2 y = \ln \left (x \right ) x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+4 x y^{\prime }+3 y = \left (x -1\right ) \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}4 x^{3} y^{\prime \prime \prime }+8 x^{2} y^{\prime \prime }-x y^{\prime }+y = x +\ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}3 x^{3} y^{\prime \prime \prime }+4 x^{2} y^{\prime \prime }-10 x y^{\prime }+10 y = \frac {4}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+7 x^{3} y^{\prime \prime \prime }+9 x^{2} y^{\prime \prime }-6 x y^{\prime }-6 y = \cos \left (\ln \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-2 x^{2} y^{\prime \prime }-x y^{\prime }+4 y = \sin \left (\ln \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )-x \left (t \right ) = \cos \left (t \right ), y^{\prime }\left (t \right )+y \left (t \right ) = 4 t]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+5 x \left (t \right ) = 3 t^{2}, y^{\prime }\left (t \right )+y \left (t \right ) = {\mathrm e}^{3 t}]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+2 x \left (t \right ) = 3 t, x^{\prime }\left (t \right )+2 y^{\prime }\left (t \right )+y \left (t \right ) = \cos \left (2 t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )-x \left (t \right )+y \left (t \right ) = 2 \sin \left (t \right ), x^{\prime }\left (t \right )+y^{\prime }\left (t \right ) = 3 y \left (t \right )-3 x \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[2 x^{\prime }\left (t \right )+3 x \left (t \right )-y \left (t \right ) = {\mathrm e}^{t}, 5 x \left (t \right )-3 y^{\prime }\left (t \right ) = y \left (t \right )+2 t]
\] |
✓ |
✓ |
|
\[
{}[5 y^{\prime }\left (t \right )-3 x^{\prime }\left (t \right )-5 y \left (t \right ) = 5 t, 3 x^{\prime }\left (t \right )-5 y^{\prime }\left (t \right )-2 x \left (t \right ) = 0]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 3 x \left (t \right ), y^{\prime }\left (t \right ) = 2 x \left (t \right )+3 y \left (t \right ), z^{\prime }\left (t \right ) = 3 y \left (t \right )-2 z \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = k^{2} y
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+k^{2} x = 0
\] |
✓ |
✓ |
|
\[
{}y^{3} y^{\prime \prime }+4 = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime } = \frac {k^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime } = x^{2}+1
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y^{\prime \prime } = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+2 x \left (1+y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = {y^{\prime }}^{3}+y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+x = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+t x^{\prime } = t^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime } = x y^{\prime }+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 1+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }+x y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = {y^{\prime }}^{2}+y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+1+{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+1 = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2} = y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}2 y y^{\prime \prime }-{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 {y^{\prime }}^{2} = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}\left (1+y\right ) y^{\prime \prime } = 3 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \sec \left (x \right ) \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime } = {\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = {y^{\prime }}^{2} \cos \left (x \right )
\] |
✗ |
✗ |
|
\[
{}y y^{\prime \prime }-y^{\prime } y^{2} = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+1+{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = y^{3}+{y^{\prime }}^{2}
\] |
✗ |
✓ |
|
\[
{}\left (1+{y^{\prime }}^{2}\right )^{2} = y^{2} y^{\prime \prime }
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime } = {y^{\prime }}^{2} \sin \left (x \right )
\] |
✓ |
✗ |
|
\[
{}2 y y^{\prime \prime } = y^{3}+2 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-k^{2} x = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = 2 {y^{\prime }}^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (1-{\mathrm e}^{x}\right ) y^{\prime \prime } = {\mathrm e}^{x} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}4 y^{2} = x^{2} {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (x +y\right ) y^{\prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}1+\left (2 y-x^{2}\right ) {y^{\prime }}^{2}-2 y {y^{\prime }}^{2} x^{2} = 0
\] |
✗ |
✗ |
|
\[
{}x \left ({y^{\prime }}^{2}-1\right ) = 2 y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (1-y^{2}\right ) {y^{\prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (x y-1\right ) y^{\prime } = y
\] |
✗ |
✗ |
|
\[
{}y^{2} {y^{\prime }}^{2}+x y y^{\prime }-2 x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-2 x y y^{\prime }+2 y^{2} = x^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+\left (x +y-2 x y\right ) {y^{\prime }}^{2}-2 y^{\prime } x y \left (x +y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+\left (y^{2}-x^{3}-x y^{2}\right ) y^{\prime }-x y \left (x^{2}+y^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y = y^{\prime } x \left (1+y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y = x +3 \ln \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y \left (1+{y^{\prime }}^{2}\right ) = 2
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}-2 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+y^{2} = 1
\] |
✓ |
✓ |
|
\[
{}x \left ({y^{\prime }}^{2}-1\right ) = 2 y y^{\prime }
\] |
✓ |
✓ |
|